2004
DOI: 10.1111/j.1751-1097.2004.tb00106.x
|View full text |Cite
|
Sign up to set email alerts
|

Phototoxic Effect of Visible Light on Porphyromonas gingivalis and Fusobacterium nucleatum: An In Vitro Study

Abstract: The antibacterial effect of visible light irradiation combined with photosensitizers has been reported. The objective of this was to test the effect of visible light irradiation without photosensitizers on the viability of oral microorganisms. Strains of Porphyromonas gingivalis, Fusobacteriurm nucleatum, Streptococcus mutans and Streptococcus faecalis in suspension or grown on agar were exposed to visible light at wavelengths of 400–500 nm. These wavelengths are used to photopolymerize composite resins widely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 28 publications
3
29
0
1
Order By: Relevance
“…photodynamic treatment) has been reported in the literature (Wilson, 1994;Henry et al, 1995Henry et al, , 1996Konig et al, 2000;Soukos et al, 2005), and it has been suggested that this effect is mediated through the production of ROS (Gourmelon et al, 1994). This hypothesis is further supported by the observation that obligate anaerobic oral bacteria (pigmented and non-pigmented) are more susceptible to blue light exposure treatment than facultative ones (Feuerstein et al, 2004;Sterer & Feuerstein, 2005). Various studies have reported that using the colourant erythrosine B as a photosensitizer enhances the antimicrobial properties of blue light from light-emitting diode (LED) or halogen light sources (De Lucca et al, 2012;Lee et al, 2012).…”
Section: Discussionsupporting
confidence: 52%
“…photodynamic treatment) has been reported in the literature (Wilson, 1994;Henry et al, 1995Henry et al, , 1996Konig et al, 2000;Soukos et al, 2005), and it has been suggested that this effect is mediated through the production of ROS (Gourmelon et al, 1994). This hypothesis is further supported by the observation that obligate anaerobic oral bacteria (pigmented and non-pigmented) are more susceptible to blue light exposure treatment than facultative ones (Feuerstein et al, 2004;Sterer & Feuerstein, 2005). Various studies have reported that using the colourant erythrosine B as a photosensitizer enhances the antimicrobial properties of blue light from light-emitting diode (LED) or halogen light sources (De Lucca et al, 2012;Lee et al, 2012).…”
Section: Discussionsupporting
confidence: 52%
“…Also, light irradiation alone (240 s) had no effect on E. faecalis but reduced F. nucleatum viability by approximately 10%. This strain was shown to possess several intracellular compounds such as cytochromes or flavins, which may have acted as endogenous photosensitizers [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…For example Feursteinet et al,1) showed that broadband blue light sources at 400-500nm exert a phototoxic effect on P. gingivalis and F. nucleatum, and Henry et al,2) demonstrated that low fluencies of argon laser irradiation (488-514 nm) exert a phototoxic effect on Porphyromonas and Prevotella spp., which are both Gram negative anaerobic bacteria that produce porphyrins. Oral black-pigmented bacteria (BPB) in pure cultures and in dental plaque samples were killed by 4.2 J/cm 2 blue light, whereas P. melaninogenica required 21 J/cm 2 .…”
Section: Introductionmentioning
confidence: 99%